2006
DOI: 10.1093/brain/awl299
|View full text |Cite
|
Sign up to set email alerts
|

Right ventromedial prefrontal lesions result in paradoxical cardiovascular activation with emotional stimuli

Abstract: Ventromedial prefrontal cortex (VMPFC) lesions can alter emotional and autonomic responses. In animals, VMPFC activation results in cardiovascular sympathetic inhibition. In humans, VMPFC modulates emotional processing and autonomic response to arousal (e.g. accompanying decision-making). The specific role of the left or right VMPFC in mediating somatic responses to non-arousing, daily-life pleasant or unpleasant stimuli is unclear. To further evaluate VMPFC interaction with autonomic processing of non-stressf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
0
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 61 publications
3
36
0
5
Order By: Relevance
“…In experiments investigating effects of positive or negative emotional stimuli on heart rate in those with a variety of lesions including head trauma, arteriovenous malformations, tumors, or stroke confined either to the right or left ventromedial prefrontal cortex (VMPFC) the results indicated that those with left sided lesions showed a blunted response (little heart rate change to emotional visual content compared to the decrease seen in controls) whereas those with right ventromedial prefrontal VMPFC cortical lesions had evidence of increased cardiovascular sympathetic responses (increased heart rate response compared to controls) (134). A rating scale indicated that the emotional content perceived by those in the three groups was similar.…”
Section: Human Functional Studiesmentioning
confidence: 98%
“…In experiments investigating effects of positive or negative emotional stimuli on heart rate in those with a variety of lesions including head trauma, arteriovenous malformations, tumors, or stroke confined either to the right or left ventromedial prefrontal cortex (VMPFC) the results indicated that those with left sided lesions showed a blunted response (little heart rate change to emotional visual content compared to the decrease seen in controls) whereas those with right ventromedial prefrontal VMPFC cortical lesions had evidence of increased cardiovascular sympathetic responses (increased heart rate response compared to controls) (134). A rating scale indicated that the emotional content perceived by those in the three groups was similar.…”
Section: Human Functional Studiesmentioning
confidence: 98%
“…14 Left VMPFC lesions result in dampened heart rate or blood pressure adjustment to visual emotional stimuli, whereas right-sided VMPFC lesions bear a risk of exaggerated cardiovascular responses with paradoxical heart rate and blood pressure increase. 14 Similarly, lateralized effects on resting cardiovascular modulation have been observed after insular stroke. 11,[15][16][17] Zamrini et al 18 and Hilz et al 19 observed a hemispheric dominance of sympathetic or parasympathetic activity in temporal lobe epilepsy patients who underwent hemispheric inactivation during the so-called WADA testing procedure before epilepsy surgery.…”
mentioning
confidence: 90%
“…An ischemiainduced decrease in sympathetic temporal lobe contribution to autonomic balance is likely to result in a shift toward cardiovagal predominance which then facilitates bradycardia or even asystole. 14,19 Surprisingly, Rincon and coworkers could not confirm a dominant association of the insular cortex with increased mortality. Some of the discrepancy to findings by Oppenheimer and coworkers 21 might be due to the fact that Oppenheimer deduced their conclusions from insular cortex stimulations in rodents, ie, from activation of brain areas that may be silent or dysfunctional after stroke.…”
mentioning
confidence: 96%
“…The spectral power of the HRV was calculated in the low frequency (LF: 0.04-0.15 Hz) and high frequency (HF: 0.15-0.4 Hz) ranges [20,21]. The fluctuation of HR in the LF range is influenced by the baroreceptor system, and reflects both sympathetic and parasympathetic activity [22]. The fluctuation of HR in the HF range is mainly related to parasympathetic efferent activity.…”
Section: Discussionmentioning
confidence: 99%